Analisis Motivasi Belajar Mahasiswa Penerima Beasiswa KIP-Kuliah Pada Mahasiswa Program Studi Pendidikan Ekonomi - Lestari Burhanudin; Amjad Salong; Silvia Manuhuttu (Universitas Pattimura, 2025)
Learning motivation is a key determinant of students’ academic success, including those receiving the KIP-Kuliah scholarship. Despite being selected based on merit, some students show academic instability across semesters. This study aims to analyze the learning motivation of KIP-Kuliah recipients in the 2020–2021 cohort of the Economic Education Study Program. A descriptive qualitative approach was employed, with data collected through unstructured interviews and documentation from four purposively selected students. The main findings reveal that while most students demonstrate an intrinsic desire to succeed, inconsistent academic behavior persists, such as tardiness, lack of discipline, and inadequate learning environments. Both internal and external factors significantly influence fluctuations in GPA. It is thus crucial for institutions to foster a supportive academic ecosystem by providing adequate learning facilities and recognizing positive behaviors. Academic mentoring programs focusing on sustained motivation development are also recommended as part of a long-term strategy.